(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The purpose of the study is to determine the contribution of the textile industry to the household income and to determine the problems confronted by textile industry in Nangarhar province. The results of the study indicate that the textile industry is in a challenging situation, it means the lack of infrastructure, lack of financial resources, lack of skilled labors, lack of security, suitable technology and marketing problems are considered to be the key challenges to the development of the industry. Furthermore, the study indicates that the effects of income from textile industries on the total household income of the targeted population are statistically significant. It means that textile industry is one of the main factors affecting the total income of the households in the target area. Textile industry is a fundamental source of income generation and employment in the study area.